MANAGERIAL INTELLIGENCE a clinical perspective. (CAMBRIDGE SCHOLARS PUBLIS, 2019)
This volume condenses over 60 years of clinical efforts with thousands of individuals in hundreds of organizations into a set of clear, concise, understandable principles and concepts that can be applied by managers to improve their performance and the performance of their organizations. Through multiple examples and illustrations, a framework is presented that enables managers to master the executive role.While there are many books that purport to provide methods or processes for managerial and executive development, most are based on empirical research efforts, or are largely anecdotal in na.